Retroperitoneal Liposarcoma Presenting With Malignant Gastric Outlet Obstruction and Acute Pancreatitis: A Case Report - Recinos, Luisa M (Cureus, 2021)
Dedifferentiated liposarcomas (DDLPS) are rare, high-grade malignancies that usually originate in the retroperitoneum. Frequently, they present as asymptomatic masses, abdominal distention, abdominal pain, and weight loss. They tend to grow significantly and are usually large in size at the time of diagnosis. Surgical resection is the mainstay of treatment; however, local recurrence is common. When unresectable, they can invade local structures and produce a significant mass effect on the adjacent organs. Here we present the first case of malignant gastric outlet obstruction (MGOO) and acute pancreatitis from a retroperitoneal DDLPS.